Modified Variational Iteration Method with Chebyshev Polynomials for Solving 12th order Boundary Value problems - Disu A. B; Jonathan Tsetimi; Ogeh K.O (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
We consider in this paper an illustration of the modified variational iteration method (MVIM) as an effective and accurate solver of 12th order boundary value problem (BVP). For this reason, the Chebyshev polynomials of the principal kind was utilized as a premise capabilities in the guess of the logical capability of the given issue. The strategy is applied in an immediate manner without utilizing linearization or irritation. The subsequent mathematical confirmations recommend that the strategy is without a doubt successful and exact as applied to a few direct and nonlinear issues as mathematical trial and error. Maple 18 was used for all computational simulations carried out in this research.©2022 JNSMR UIN Walisongo. All rights reserved.